2022
DOI: 10.1080/10643389.2022.2083897
|View full text |Cite
|
Sign up to set email alerts
|

Abiotic transformation of polycyclic aromatic hydrocarbons via interaction with soil components: A systematic review

Abstract: HAL is a multi-disciplinary open access archive for the deposit and dissemination of scientific research documents, whether they are published or not. The documents may come from teaching and research institutions in France or abroad, or from public or private research centers. L'archive ouverte pluridisciplinaire HAL, est destinée au dépôt et à la diffusion de documents scientifiques de niveau recherche, publiés ou non, émanant des établissements d'enseignement et de recherche français ou étrangers, des labor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(2 citation statements)
references
References 142 publications
0
2
0
Order By: Relevance
“…[ [168][169][170] Thermal desorption Heating contaminated soil to volatilize PAHs for capture and treatment.…”
Section: Strategies For Pahs Control Using Green Technologiesmentioning
confidence: 99%
“…[ [168][169][170] Thermal desorption Heating contaminated soil to volatilize PAHs for capture and treatment.…”
Section: Strategies For Pahs Control Using Green Technologiesmentioning
confidence: 99%
“…Previous studies found that reactive Fe minerals and OM might be the vital constituents in soils for O 2 system to evolve reactive species and attain the transformative removal of pollutants. 55,56 Likewise, these reactive constituents might be a PS activator due to higher redox potential and smaller peroxide bond dissociation energy of PS (2.08 V, 92 kJ mol −1 ) than that of O 2 (1.23 V, 498.36 kJ mol −1 ). In our study, OM removal through H 2 O 2 treatment had negligible influence on SMX degradation in the IPS/PS system; OM removal led to a slight decrease of SMX degradation in IRS1/PS (11.0%) and IRS2/ PS (15.6%) systems (Figure 2b).…”
Section: Identification Of Soil-inherent Minerals and Thementioning
confidence: 99%